Formicamycin biosynthesis involves a unique reductive ring contraction. Issue 31 (17th June 2020) - Qin, Zhiwei; Devine, Rebecca; Booth, Thomas J.; Farrar, Elliot H. E.; Grayson, Matthew N.; Hutchings, Matthew I.; Wilkinson, Barrie
Abstract : Using a combination of biomimetic chemistry and molecular genetics we demonstrate that formicamycin biosynthesis proceeds via reductive Favorskii-like reaction. Abstract : Fasamycin natural products are biosynthetic precursors of the formicamycins. Both groups of compounds are polyketide natural products that exhibit potent antibacterial activity despite displaying different three-dimensional topologies. We show here that transformation of fasamycin into formicamycin metabolites requires two gene products and occurs via a novel two-step ring expansion-ring contraction pathway. Deletion of forX, encoding a flavin dependent monooxygenase, abolished formicamycin production and leads to accumulation of fasamycin E. Deletion of the adjacent gene forY, encoding a flavin dependent oxidoreductase, also abolished formicamycin biosynthesis and led to the accumulation of new lactone metabolites that represent Baeyer–Villiger oxidation products of the fasamycins. These results identify ForX as a Baeyer–Villiger monooxygenase capable of dearomatizing ring C of the fasamycins. Through in vivo cross feeding and biomimetic semi-synthesis experiments we showed that these lactone products represent biosynthetic intermediates that are reduced to formicamycins in a unique reductive ring contraction reaction catalyzed by ForY.